1992
DOI: 10.1007/bf00210737
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen with type-I mutation is polymorphic in the Japanese population

Abstract: A functionally inactive plasminogen (PLG) variant designated as PLG M5 is polymorphic in the Japanese population and has a feature common to PLG with type-I mutation that has a codon 601 missense mutation in exon 15 (GCT for Ala-->ACT for Thr). This study was conducted to clarify whether the type-I mutation of PLG is present in PLG M5 and polymorphic in the Japanese population. Direct sequencing of the amplified DNA from the PLG gene in a heterozygote for PLG M5 revealed that the sequence of the exon 15 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…The development of fibrin deposits in Plg-/-mice is consistent with the severe thrombotic problems reported in patients identified with dysplasminogenemia (Aoki et al 1978;Ichinose et al 1991;Kikuchi et al 1992;Robbins 1992;Azuma et al 1993) and hypoplasminogenemia (Lottenberg et al 1985;Girolami et al 1986;Mannucci et al 1986;Dolan et al 1988;Patrassi et al 1993), which include recurring venous thrombosis, pulmonary hypertension, retinopathy, and stroke. However, the total deficit of Pig established in transgenic mice is distinct from any known Plg disorder in human patients.…”
Section: Genes and Developmentsupporting
confidence: 75%
See 2 more Smart Citations
“…The development of fibrin deposits in Plg-/-mice is consistent with the severe thrombotic problems reported in patients identified with dysplasminogenemia (Aoki et al 1978;Ichinose et al 1991;Kikuchi et al 1992;Robbins 1992;Azuma et al 1993) and hypoplasminogenemia (Lottenberg et al 1985;Girolami et al 1986;Mannucci et al 1986;Dolan et al 1988;Patrassi et al 1993), which include recurring venous thrombosis, pulmonary hypertension, retinopathy, and stroke. However, the total deficit of Pig established in transgenic mice is distinct from any known Plg disorder in human patients.…”
Section: Genes and Developmentsupporting
confidence: 75%
“…Interestingly, simple heterozygosity for either Plg deficiency (with half-normal Plg activity and antigen) or dysplasminogenemia (with half-normal Plg activity but normal antigen) appears to be associated with thrombotic tendency requiring clinical treatment. However, other factors, such as infection, injury, or vascular disease, are likely to contribute to this tendency, as only a subset of heterozygotes, even within the same family, suffer from thrombosis (Aoki et al 1978;Girolami et al 1986;Dolan et al 1988;Kikuchi et al 1992;Robbins 1992;Azuma et al 1993;Patrassi et al 1993). Remarkably, one form of dysplasminogenemia (type-l, Ala 6~ ~ Thr) occurs with an estimated gene frequency of -2% in the Japanese population (Kikuchi et al 1992), but few homozygous patients (-10% residual activity; Aoki et al 1978) have ever been identified (Aoki et al 1978;Ichinose et al 1991;Kikuchi et al 1992).…”
Section: Genes and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, by isoelectric focusing electrophoresis, several workers identified a functionally inactive PLG variant designated PLG M5, and demonstrated that PLG Tochigi and PLG Nagoya II are identical and has a feature common to PLG M5 with an Ala601Thr point mutation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Compound heterozygosity for plg 453N/D correlates with an equal 'mixture' of IEF plg phenotypes A and B, which was previously described as a distinct phenotype and designated AB [10]. Furthermore, it has been shown that dysplasminogenemia due to plg mutation A601T leads to IEF phenotype M5 ( plg Tochigi) [11,12]. Distinct aberrant new IEF band patterns have been also described in three patients with hypoplasminogenemia due to the presence of a K19E mutation in a homozygous or compound heterozygous state [10].…”
Section: Introductionmentioning
confidence: 95%